Cross‐level effects of support climate: Main and moderating roles. Issue 5 (9th January 2018) - Takeuchi, Riki; Way, Sean A.; Tian, Amy Wei
Abstract : Using a sample composed of 701 food and beverage managers nested in 120 units and 40 Asian hotel properties, in the current study we investigated the effects of unit high‐performance work system (HPWS) use and unit support climate on individual unit members' human resource outcomes (job performance behaviors: in‐role and organizational citizenship behaviors). The results support the hypothesized relationships among unit HPWS use, unit support climate, individual affective commitment, and individual job performance behaviors. The current study's findings illuminate the ways (e.g., mediation and moderation) in which the unit support climate advances positive organizationally relevant individual‐level human resource outcomes. Findings, implications, and limitations as well as avenues for future research are discussed.